Dipolar Interactions: Direct Detection of Static Dipolar Interaction on a Single Nanodisk Using Microfocused Brillouin Light Scattering Spectroscopy (Adv. Electron. Mater. 5/2015). (May 2015) - Shimon, Goei; Adeyeye, Adekunle O.
<x xml:space="preserve">Abstract</x> In article number 1500070, G. Shimon and A. O. Adeyeye quantified the effects of the neighboring static dipolar interactions on the dynamic behavior of a single disk using Brillouin light scattering spectroscopy. Different modes of interaction are distinguished depending on the inter‐disk coupling orientation with respect to the applied field. This work is useful in further development of high‐density magnetic recording media, functional microwave signal processing, and logic devices.